Archaeological survey at Balama Byzantine Castle in Pisidia (southwest Turkey): a preliminary report - Hüseyin Metin; Abdulhadi Durukan (Polish Archaeology in the Mediterranean)
The ancient region of Pisidia, located in southwest Turkey, has a settlement history extending from the Prehistoric period to the end of the Byzantine era. Numerous settlements established in this area lay along the Via Sebaste — a vital route connecting the East and the West. During the Roman period, socio-cultural development flourished there with the spread of colonization. Later, as part of the Byzantine Empire, Pisidia, became a focal point of political and social conflict due to its strategic position, leading to the construction of fortified settlements in strategically important rural areas to ensure their defense. Among these settlements is Balama Castle, situated atop a commanding hill. The site features houses, cisterns, churches, and fortification walls with towers placed at regular intervals. The walls, constructed of rubble stone, lime mortar, and broken bricks, suggest that the fortifications were constructed in no specific order. The main goal was apparently to quickly build defensive structures to protect the region. Balama Castle was not a renovation of an earlier structure but a part of a newly developed defense system. This system, created by the Byzantines in the 11th century AD, remained in use through the 12th century AD. Balama Castle, dating to the Middle Byzantine period, was identified during an archaeological survey conducted in the region in 2017. This study serves as a preliminary report presenting the initial findings from the site.